The SWOT-TOWS analysis as a tool of the PDCA cycle in improving the quality of the postal service - Kowalik, Kamila (Journal of Education, Health and Sport, 2020)
The purpose of the study is the practical application of the SWOT-TOWS analysis as a PDCA cycle in improving the quality of postal services. The first part of the article contains a review of the literature on the issues of service quality in relation to postal services and the characteristics of the selected tool - the PDCA cycle. Then, the results of the research have been presented, i.e. the SWOT-TOWS analysis of the chosen postal operator and its importance in the PDCA cycle to improve the quality of postal services. The analysis has showed that the chosen operator should adopt a conservative operating strategy which means the need to minimize threats by using strengths. In view of these data, actions should be taken to improve the quality of services with particular emphasis on digital postal services.